Zearalenone and its metabolites: Effect on human health, metabolism and neutralisation methods. (15th April 2019) - Rogowska, A.; Pomastowski, P.; Sagandykova, G.; Buszewski, B.
Abstract: Mycotoxins are natural compounds produced as secondary metabolites by mold fungi belonging mainly to the Fusarium family, commonly found on plants such as corn or small grains in the temperate climate zone. One of these mycotoxins is zearalenone, which is classified as a xenoestrogen, an exogenous compound which resembles the structure of naturally occurring estrogens with its chemical structure. This property of zearalenone determines its ability to bind to estrogen receptors of cell and its bioaccumulation. This leads to disorders of the hormonal balance of the body, which in consequence may lead to numerous diseases of reproductive system such as prostate, ovarian, cervical or breast cancers. High risk posed by long-term exposure to contaminated food forces the modern science to develop and implement effective methods of zearalenone neutralisation. This work is a review of current state of knowledge on toxic effects of zearalenone, its metabolism in biological systems and proposed methods of its neutralisation. Highlights: Occurrence and effect of zearalenone on human and animal organisms. Metabolic pathways of zearalenone in various biological systems. Physical, chemical and biological methods of neutralization of zearalenone and other mycotoxins from food and feeds.